2018
DOI: 10.1001/jamaophthalmol.2018.1804
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Intravitreal Aflibercept for Polypoidal Choroidal Vasculopathy in the PLANET Study

Abstract: IMPORTANCE Polypoidal choroidal vasculopathy (PCV) is common in Asian populations, but an optimal treatment approach remains to be confirmed. OBJECTIVE To evaluate intravitreal aflibercept injection (IAI) in participants with PCV and compare IAI monotherapy with IAI plus rescue photodynamic therapy (PDT). DESIGN, SETTING, AND PARTICIPANTS This 96-week, double-masked, sham-controlled phase 3b/4 randomized clinical trial was conducted at multiple centers in Australia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
244
3
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(263 citation statements)
references
References 27 publications
9
244
3
7
Order By: Relevance
“…The mean number of injections was 7.3 (EVEREST-II) and 8.1 (PLANET). 4,5 These results were corroborated further by the DRAGON study, 126 a phase 4 randomized, double-masked, multicenter trial based in China comparing the efficacy of IVT-R monotherapy using a monthly fixed dosing regimen versus a pro re nata regimen. 126 At baseline, 41.7% of the 334 enrolled patients were diagnosed with PCV based on ICGA results.…”
Section: Key Clinical Trialsmentioning
confidence: 79%
See 1 more Smart Citation
“…The mean number of injections was 7.3 (EVEREST-II) and 8.1 (PLANET). 4,5 These results were corroborated further by the DRAGON study, 126 a phase 4 randomized, double-masked, multicenter trial based in China comparing the efficacy of IVT-R monotherapy using a monthly fixed dosing regimen versus a pro re nata regimen. 126 At baseline, 41.7% of the 334 enrolled patients were diagnosed with PCV based on ICGA results.…”
Section: Key Clinical Trialsmentioning
confidence: 79%
“…Recently, the first-year results of 2 major randomized trials have been released and have provided new evidence on optimal treatment for PCV: EVEREST-II compared intravitreal ranibizumab (IVT-R) monotherapy with combination therapy comprising IVT-R plus photodynamic therapy (PDT), whereas the PLANET study compared intravitreal aflibercept (IVT-AFL) monotherapy with or without rescue PDT. 4,5 The aim of this review was to summarize the latest evidence on the diagnosis and management of PCV, covering epidemiologic and risk factors, pathogenesis, definition and classification, and management options and to propose up-to-date management guidelines for clinicians managing patients with this condition.…”
mentioning
confidence: 99%
“…The EVEREST II study found that combination therapy of full-dose PDT and intravitreal injections of ranibizumab was superior to monotherapy consisting of intravitreal injections of ranibizumab, in terms of BCVA and complete polyp regression [40]. However, recent studies suggest that anti-VEGF monotherapy with, for example, aflibercept has similar efficacy, at least in an Asian population [41,42].…”
Section: Specific Considerations When Treating Polypoidal Choroidal Vmentioning
confidence: 99%
“…Treatments may include thermal laser (reserved for extrafoveal polyps), photodynamic therapy (PDT) and anti‐vascular endothelial growth factor (anti‐VEGF) injections . Combination therapy with anti‐VEGF and PDT has been evaluated in the recently published randomized controlled trials EVEREST II and PLANET studies, respectively . Surgery is generally reserved for complicated cases, and in particular, subretinal with or without vitreous haemorrhage.…”
mentioning
confidence: 99%
“…EVEREST II suggested that ranibizumab combined with PDT offered superior visual outcomes than anti‐VEGF monotherapy by around three ETDRS letters, required fewer injections (four vs seven), and had double the polyp closure rate (70% vs. 35%) at 12 months . PLANET reported that aflibercept monotherapy was a suitable treatment of PCV (85% of patients were dry and inactive at 1 year) and most cases demonstrated a prompt and significant clinical benefit, with few patients (<15%) requiring rescue PDT . Three cases of vitreous haemorrhage were reported in EVEREST II from 322 eyes (two in the monotherapy arm and one in the combination arm), but it is not clear if this was related to submacular haemorrhage and breakthrough or some other cause .…”
mentioning
confidence: 99%